2017
DOI: 10.1039/c7ra06851d
|View full text |Cite
|
Sign up to set email alerts
|

High temperature resistant polysulfone/silica double-wall microcapsules and their application in self-lubricating polypropylene

Abstract: Fabrication and application of high temperature resistant polysulfone/silica double-wall microcapsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…And microencapsulation technology has signicant effects on the protection of plant essential oils, improving the stability of essential oils and their controlled release. [8][9][10][11] Therefore, the selection of shell materials is particularly important. b-CD is an enzymatically modied starch, shaped like a hollow cone, which has been widely used for the encapsulation of essential oils, giving some of the highest encapsulation yields, due to the formation of inclusion complexes between the oil and the apolar cavity of CD.…”
Section: Introductionmentioning
confidence: 99%
“…And microencapsulation technology has signicant effects on the protection of plant essential oils, improving the stability of essential oils and their controlled release. [8][9][10][11] Therefore, the selection of shell materials is particularly important. b-CD is an enzymatically modied starch, shaped like a hollow cone, which has been widely used for the encapsulation of essential oils, giving some of the highest encapsulation yields, due to the formation of inclusion complexes between the oil and the apolar cavity of CD.…”
Section: Introductionmentioning
confidence: 99%
“…Then the n ‐octadecane core mixed the broken TiO 2 shell fragments and epoxy debris to backfill the pits and cracks (Figure 13C) [ 53,54 ] . In the meantime, the mixture of n ‐octadecane, TiO 2 and epoxy debris formed transfer film in the interfaces between ball and wear surface during continuous friction (Figure 13D) [ 55,56 ] , which contributed to the lowest of COF among three samples.…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent this problem, the encapsulated lubricant technology has been considered as emerged technology for realization of liquid lubricant into practical application of self-lubrication. [12,13] Yang et al [14] incorporated the silica gel shell microcapsule containing ionic liquid into the PU matrix, which showed that the ionic liquid released from the broken microcapsule can effectively the corresponding PU materials. The paraffin oil entrapped in the closed cell of materials without follow-up removal, which realizes the one-pot synthesis of oil-containing self-lubricating PU materials.…”
Section: Introductionmentioning
confidence: 99%